The Effect Of Product Innovation And Business Competition On The Development Of MSMES In Harjosari I Substance, Medan Amplas - Apriyani Hizriah Hsb (Movere Journal, 2022)
This study analyzes the effect of product innovation and business competition simultaneously on the development of MSMEs in Harjosari I Village, Medan Amplas District. The population in this study were all MSMEs in Harjosari I Medan Amplas Village as many as 62 MSMEs. Saturated sampling technique is a sampling technique when all members of the population are used as samples. Since the number of MSMEs in Harjosari I Medan Amplas Village is 62 MSMEs (less than 100 people), all MSMEs are taken as objects of research. The place of this research was conducted on Jl. Sisingamangaraja, Jl. Garu I to Garu VIII, Harjosari I Village, Medan Sandpaper. The time of this research starts in October 2021 until March 2022. The research method used in this study is the method of observation, documentation and questionnaires using a Likert scale. The analytical method used is the multiple linear regression method using the SPSS program. The results of the research with a partial test that Product Innovation has a t value of 4.714 > 1.6698, so it can be concluded that the Product Innovation variable has a positive and significant impact on the development of MSMEs in Harjosari I Village, Medan Amplas District. Business Competition has a t-count value of 3.704 > 1.6698, so it can be concluded that Business Competition has a positive and significant effect on the development of MSMEs in Harjosari I Village, Medan Amplas District. Based on the results of the F test (simultaneous) that jointly Product Innovation and Business Competition have a positive and significant impact on the development of MSMEs in Harjosari I Village, Medan Amplas District with a value of F count > F Table (41.430 > 3.15). The results of the analysis of the coefficient of determination (R2) indicate that Product Innovation and Business Competition have an influence on the development of MSMEs in Harjosari I Village, Medan Amplas District with a value of 58.4%, while the remaining 41.6% is influenced by other variables not examined in the study. this